Odpowiedzi

Najlepsza Odpowiedź!
2009-12-21T15:20:59+01:00
(2⁵:8⁶)¹⁷= (2⁵ : (2³)⁶)¹⁷ = (2⁵ :2¹²)¹⁷=(2⁵⁻¹²)¹⁷=(2⁻⁷)¹⁷=2⁻¹¹⁹ = 1/2¹¹⁹
4⁶*3¹²=4⁶ * (3²)⁶ =4⁶ * 9⁶ = (4 * 9)⁶ = 36⁶
6⁻⁷*5⁷= (1/6⁷) * 5⁷ = 5⁷/6⁷ = (5/6)⁷
(25⁴*2⁸)⁻⁷= (25⁴ * (2²)⁴) ⁻⁷ = (25⁴ * 4⁴) ⁻⁷ = ((25 * 4)⁴)⁻⁷ = (100⁴)⁻⁷ =
= 100⁻²⁸ = 1/100²⁸
(0,2⁷*5⁷)⁻³=((0,2 * 5)⁷)⁻³=(10⁷)⁻³ = 10⁻²¹ 1/10²¹
3⁸*9⁻³= 3⁸ * (3²)⁻³ = 3⁸ * 3⁻⁶ = 3⁸⁻⁶ = 3²
(7⁹:49⁻⁵)²*7⁻⁴⁰= (7⁹ : (7²)⁻⁵)² * 7⁻⁴⁰ = (7⁹ : 7⁻¹⁰) * 7⁻⁴⁰ =
= 7⁹⁺¹⁰ * 7⁻⁴⁰ = 7¹⁹ * 7⁻⁴⁰ = 7 ⁻²¹ = 1/7²¹